The Effect of Freeze/Thaw Cycles on Reproducibility of Metabolic Profiling of Marine Microalgal Extracts Using Direct Infusion High-Resolution Mass Spectrometry (HR-MS) - Hans Eilertsen; Siv Huseby; Maria Degerlund; Gunilla Eriksen; Richard Ingebrigtsen; Espen Hansen (Molecules, 2014)
During normal sample preparation, storage in freezers and subsequent freeze/thaw cycles are commonly introduced. The effect of freeze/thaw cycles on the metabolic profiling of microalgal extracts using HR-MS was investigated. Methanolic extracts of monocultures of Arctic marine diatoms were analyzed immediately after extraction, after seven days of storage at −78 °C (one freeze/thaw cycle), and after additional seven days at −20 °C (two freeze/thaw cycles). Repeated direct infusion high-resolution mass spectrometry analysis of microalgae extracts of the same sample showed that reproducibility was ca. 90% when a fresh (unfrozen) sample was analyzed. The overall reproducibility decreased further by ca. 10% after the first freeze/thaw-cycle, and after one more freeze/thaw cycle the reproducibility decreased further by ca. 7%. The decrease in reproducibility after freeze-thaw cycles could be attributed to sample degradation and not to instrument variability.